Antitumor Potential and other Emerging Medicinal Properties of Natural Compounds - Fang, Evandro Fei.; Ng, Tzi Bun. (Springer Netherlands : Imprint: Springer, 2013)
The modern unhealthy diet and lifestyle in conjunction with pathogens, environmental carcinogens and multiple other risk factors increase humans susceptibility to different diseases exemplified by elevated levels of cancers, cardiovascular and communicable diseases. Screening of potential drugs from medicinal plants and animals provides a promising strategy for the alleviation of the impact of these diseases. Components with potential medicinal applications include RIPs, RNases, lectins, protease inhibitors and numerous small compounds. These compounds have shown both preventive and therapeutic effects for humans. This book is a compilation of articles written by internationally renowned experts exploring the different uses of medicinal compounds in human therapeutics. Here we provide a comprehensive outlook on both qualitative and quantitative studies focusing on medicinal plants and animals, and establishing a link between laboratory research discovery and clinical applications.